Assessing the Development of Operator Trust in Automation: A Longitudinal Study of an Autonomous Campus Shuttle. (December 2020) - Fowler, Margaret; Sasangohar, Farzan; Brydia, Bob
A large public tier-1 university hosted an autonomous vehicle on campus for a 12-week demonstration. Throughout the deployment, the vehicle was operated autonomously and used 5 safety operators from the student population to take over shuttle operations, as necessary. Daily and weekly surveys as well as pre-and post-study interviews were used to investigate how operators' trust developed and changed over time as well as the relationship between trust and operational issues that varied in severity. Results revealed that there was not a significant relationship between trust and severity of operational issues. Trust levels appeared to remain relatively consistent before, during and after the deployment.